UV Weathering of Green Composites Based on Polyamide 6 (PA6) and Sunflower Seed (Helianthus Annuus L.) Husk, Pistachio (Pistacia Vera L.) Shell and Walnut (Juglans Regia L.) Shell Flour - Emel Kuram; Fatih Aydınlı; Ömer Faruk Akkuzu; Babür Özçelik (Gazi Üniversitesi Fen Bilimleri Dergisi)
Current research aims to evaluate agricultural shells' potential for use at outdoor applications by determining the ultraviolet (UV) ageing of agricultural shell filled composites. Therefore, in current work, three different agricultural shells were utilized as natural fillers in the production of polyamide 6 (PA6) based composites. Dakota type sunflower seed husk, walnut shell and pistachio shell were employed as natural fillers. It was concluded that the tensile behavior of PA6 altered from ductile to brittle after the loading of pistachio shell, sunflower seed husk and walnut shell flour. Although the agricultural shell flour decreased tensile strength of pure PA6 polymer, the strength values were still acceptable in some applications and low price of agricultural shell flour filled PA6 composites made them feasible. In general, tensile strength increased slightly after UV ageing in agricultural shell flour filled PA6 composites. The highest increase was found with the 24-hour UV aged walnut shell flour filled PA6 composite. Although agricultural shell loading led to decrement in tensile strength of PA6 polymer, fact that these composites cause little change or even an increment in the tensile strength after exposure to UV ageing indicated that agricultural shell filled composites can be utilized in outdoor conditions. UV ageing increased the flexural strength of all agricultural shell flour filled PA6 composites and this result indicated that agricultural shell filled composites can be used in outdoor conditions. Among green composites, the greatest flexural strength was achieved by the 24-hour UV aged walnut shell flour filled PA6 composite.